The Implications of Religious Peer Disagreement for Religious Epistemology A Response to Harold Netland - Beilby, James K.; Netland, Harold A. 1955- (2023)
In Religious Experience and the Knowledge of God, Harold Netland offers a helpful, balanced approach to the epistemology of religious experience. The value of Netland's volume notwithstanding, I offer a critique of Netland's claims regarding the identification of epistemic peers, the epistemic implications of religious peer disagreement, and the viability of the demand for additional evidence as a response to instances of peer disagreement.
Keywords: Rezension